The value-work theory through the main economic schools: a documentary approach (Papeles, 2019)
This work makes an exhibition, based on a documentary compilation, about the vision of the labor theory of value of the most representative authors of the different schools of economic thought, from the 17th century with William Petty, through Adam Smith, David Ricardo, Karl Marx, Alfred Marshall, John Keynes, among others, in order to determine the transformation that this concept has had through these. Finally, this paper concludes that the generality of the authors do not recognize a strategic o majority importance to the work as the only element of value; instead, a weighting between several elements and conceptual categories is observed. Additionally, Marx is established as the apex point of the theory and, in addition, as the inflection point, where the labour theory of value gradually leaves the strategic importance of the labour.
Keywords: labour theory of value; schools of economic thought; conceptual development